Pharmacokinetics and analgesic efficacy of intranasal administration of tramadol in dogs after ovariohysterectomy. (July 2020) - Di Salvo, Alessandra; Conti, Maria Beatrice; Nannarone, Sara; Bufalari, Antonello; Giorgi, Mario; Moretti, Giulia; Marenzoni, Maria Luisa; della Rocca, Giorgia
Abstract: Objective: To assess analgesic efficacy and the pharmacokinetics of intranasal (IN) tramadol in dogs following ovariohysterectomy. Study design: Randomized, blinded clinical study. Animals: A total of 30 bitches undergoing elective ovariohysterectomy. Methods: Dogs were randomly assigned to one of three experimental groups (10 dogs per group): IN tramadol 4 mg kg –1 (group T-IN), intravenous (IV) tramadol 4 mg kg –1 (group T-IV) and IV methadone 0.2 mg kg –1 (group M). Drugs were administered at extubation. At established time points (before surgery and up to 8 hours after drug administration) analgesia was assessed using the Italian version of the Glasgow Composite Measure Pain Scale Short Form and physiological variables were recorded. To determine the pharmacokinetics of IN tramadol, blood samples were collected at predetermined time points. Shapiro–Wilk test was used to assess whether data were normally distributed and consequently parametric or non parametric tests were applied. A p value < 0.05 was considered significant. Results: No significant intergroup differences were observed in the dogs that were administered rescue analgesia and time of its administration. Excluding dogs that were administered rescue analgesia, no significant intergroup differences emerged in pain scores and physiological variables, except for a lower rectal temperature in group M compared with the tramadol groups. After IN administration, tramadol was rapidly absorbed into the systemic circulation, reaching its maximum concentration (range 74.74–200.29 ng mL –1 ) within 30–60 minutes, it then decreased rapidly and was detectable in plasma for up to 2 hours after treatment in all dogs. Conclusions and clinical relevance: IN tramadol administration appears to be as effective as IV tramadol and methadone treatments in pain management of dogs after elective ovariohysterectomy. Given its low concentrations and short detection time in plasma after the IN route, systemic tramadol action appears unlikely.